Wetlands and Water Framework Directive Protection, Management and Climate Change - Ignar, Stefan; Grygoruk, Mateusz; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book compares the lessons learned from a wetland-perspective approach to the changing climate and the requirements of the Water Framework Directive (WFD) with regard to environmental conservation. Examples from Germany and Poland are discussed due to the efficiency of their respective implementations of water conservation policies. Although the general scientific interest in specific issues such as wetlands, climate change, nature conservation and the WFD enjoy a well established position in international environmental research, these four elements are rarely considered together due to the complexity of the processes, biased scenarios of global change and subjective policy background. Major challenges involved in carrying out environmental conservation actions that assess the potential impacts of climate change and management plans on water bodies are identified. The results of this approach are addressed to practitioners in the field of adaptive management in a wetlands context.
Wetlands and Water Framework Directive: protection, management and climate change -- Synergies and Conflicts between Water Framework Directive and Natura 2000: Legal requirements, technical guidance and experiences from practice -- Can Natura 2000 Sites Benefit from River Basin Management Planning Under a Changing Climate? Lessons from Germany -- Do water management and climate-adapted management of wetlands interfere in practice? Lessons from the Biebrza Valley, Poland -- Wetlands in river valleys as an effect of fluvial processes and anthropopression -- New vision of the role of land reclamation systems in nature protection and water management.
Keywords: Environment; Water; Hydrology; Physical geography; Environmental Sciences; Water; Earth System Sciences